2010
DOI: 10.1039/b927601g
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to measure diffusion coefficients in porous metal–organic frameworks

Abstract: We present a novel method to determine diffusion constants of small molecules within highly porous metal-organic frameworks (MOFs). The method is based on the recently proposed liquid-phase epitaxy (LPE) process to grow MOF thin films (SURMOFs) on appropriately functionalized substrates, in particular on organic surfaces exposed by thiolate-based self-assembled monolayers (SAMs). By applying the LPE-method to SAM-coated quartz crystals, the time-dependence of the mass-uptake of the MOF when exposing it to a ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
163
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 151 publications
(172 citation statements)
references
References 29 publications
5
163
0
4
Order By: Relevance
“…Thermodynamics of the sorption process: It has been reported that thermodynamic properties such as activation energy and Gibbs free energy of the sorption processes can be evaluated from the QCM responses [45,46]. Knowledge of these properties can be valuable as a guide to determine how to increase the response, reversibility and reproducibility of future sensing materials.…”
Section: Neutron Measurements and Distribution Of Pnt In Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermodynamics of the sorption process: It has been reported that thermodynamic properties such as activation energy and Gibbs free energy of the sorption processes can be evaluated from the QCM responses [45,46]. Knowledge of these properties can be valuable as a guide to determine how to increase the response, reversibility and reproducibility of future sensing materials.…”
Section: Neutron Measurements and Distribution Of Pnt In Filmmentioning
confidence: 99%
“…Knowledge of these properties can be valuable as a guide to determine how to increase the response, reversibility and reproducibility of future sensing materials. If we assume the diffusion of pNT into the dendrimer film follows a simple "site-hopping" model, the temperature dependence of the diffusivity can be written as [45] Page 10 of 24…”
Section: Neutron Measurements and Distribution Of Pnt In Filmmentioning
confidence: 99%
“…The QCM sensor was placed in a flow cell (Q-Sense E4). Infiltration with guest molecules was achieved via a flow of gas or a stream of liquid through the cell 25 . The SURMOF to be investigated was grown directly on the gold-coated QCM sensor after functionalization with a 16-mercaptohexadecanoic acid selfassembled monolayer (MHDA SAM).…”
Section: Uptake By Pristine Hkust-1 Surmofs Of Varying Thicknessesmentioning
confidence: 99%
“…Under adequate conditions, SURMOFs grow uniformly and film roughness as low as the size of a MOF unit cell can be achieved 23 . Apart from many potential applications, including chemical sensors and membranes, SURMOFs are well suited for a quantitative analysis of dynamic phenomena within MOFs [24][25][26] . In the present study we used HKUST-1, which is also known as Cu 3 ARTICLE commercially available 30 .…”
mentioning
confidence: 99%
“…[38][39][40] In QCM-D, the change in frequency of a quartz crystal resonator is monitored upon mass changes. The adsorbed mass, M f , and the frequency-shift, Δf n , are related by the Sauerbrey Equation (1)…”
Section: Preparation Of Nanoporous Films By Removal Of Templatementioning
confidence: 99%